AN INTRODUCTION TO TRADITIONAL MEDICINES OF SEMI ARID REGIONS: Life Science-Biology - SHARMA, SANTOSH; KUMAR, ASHWANI (International Journal of Life Science and Pharma Research, 2012)
The dependence of man on nature for food, fuel, fodder and medicines goes back to prehistoric times. The oldest civilizations have indication of plants being worshipped by man and different forms of grain are found associated with human beings globally. Initially, man was dependent on plant system for its medical needs, vitality and cure of diseases. The knowledge about plants as a source of medicine was confined to dwellers of high mountains, tribal people, village folk and priests. Now the traditional Indian system of medicine can be broadly classified into the empirical forms of folk medicine which are village based, region-specific, indigenous herb based, local resources based and in many cases, community-specific. At present moment, the pharmaceutical industries are giving much importance to Indian system of medicine to find out possible remedies because synthetic drug preparations take lot of time and is a tedious jobs